Zinc supplementation attenuate diabetic indices in patients with diabetic retinopathy - Naghizadeh, Siamak; Kheirouri, Sorayya; Ojaghi, Habib; Jafari Kaffash, Ahad (Progress in Nutrition, 2018)
Aim: Zinc (Zn) deficiency has been shown to be associated with age-related eye diseases, such as diabetic retinopathy. Blood sugar and blood pressure are prognostic factors in diabetic retinopathy. The aim of this study was to evaluate the effects of zinc supplementation on diabetes indices and blood pressure in patients with non-proliferative diabetic retinopathy. Patients and Methods: 45 patients with non-proliferative diabetic retinopathy (20 males and 25 females) aged from 40 to 70 years were participated in current double-blind randomized placebo-controlled trial. The disease was diagnosed by an expert ophthalmologist according to early photocoagulation and diabetic retinopathy criteria. The patients were assigned to intervention (23 patients) and placebo (n = 22) groups. The groups received zinc (as zinc gluconate; 30 mg) and placebo (maltodextrin; 30 mg) for 3 months, respectively. Fasting insulin, fasting glucose, insulin resistance index (HOMA-IR), hemoglobin A1c (HbA1c), systolic blood pressure (SBP), diastolic blood pressure (DBP) and serum zinc levels were measured before and after the intervention in the both groups. Results: Zinc supplementation significantly increased serum zinc (P= 0.004) and decreased serum insulin levels (P= 0.008), fasting blood sugar (FBS) (P= 0.011), HOMA-IR (P= 0.002) and SBP (P= 0.017) in the intervention group compared with placebo group. The intervention had no significant effects on DBP, HbA1c. Conclusion: Due to the positive effects of zinc supplementation on prognostic factors of diabetic retinopathy, it seems complementary therapy with zinc is needed in these patients.